AN ESSENTIAL TOOL TO BE OPTIMIZED: SYNDROMIC MANAGEMENT OF VAGINAL DISCHARGE IN HAITI - Sturgis, Morgan; Buckman, Victoria; Diawara, Samiya; St. Paul, Fiquita; Adrien, Marlene; Zhao, Xixi; Mehta, Supriya; Towbin, Jennifer; Crane, Stephanie (African Journal of Infectious Diseases (AJID), 2023)
Background: Haiti, like many low-income countries in crisis, has limited resources for etiologic diagnosis of vaginal discharge. As such, we sought to characterize variability in diagnoses of women presenting with vaginal discharge syndrome, with the goal to improve standardization of syndromic management. Materials and Methods: Participants aged 18 years and older endorsing vaginitis, or dysuria were recruited at Jerusalem Clinic over two, one-week periods in April 2018 and July 2019. We calculated Spearman rank correlations among history, exam findings, and diagnoses based on clinical presentation, to understand presentation groupings and their management. Results: Among 98 women, median age was 33.5 years, and most frequent symptoms were: vaginal discharge (97%), vaginal itch (73%), and/or suprapubic pain (68%). Most common physical exam findings were vaginal discharge (86%), suprapubic/lower quadrant tenderness (29%), cervical motion tenderness (24%), and cervical erythema (20%). Most symptoms and physical exam findings were weakly correlated with each other. Nearly one-third (31%) were diagnosed with normal physiologic vaginal discharge or no diagnosis, followed by Bacterial vaginosis (31%), vulvovaginal candidiasis (15%), cervicitis/PID (13%), and STI (7%). No reported symptoms strongly differentiated diagnostic categories. Diagnoses varied considerably by exam findings. Conclusions: The weak correlations between symptoms, exam findings, and diagnoses could represent variability in assessment. In the absence of reliable and accessible laboratory testing, the importance of standardizing syndromic management becomes increasingly relevant. Results from our study support the utility of speculum examination and more standardized documentation of physical exam findings. Next steps include the development of local algorithms to promote standardization of treatment of vaginal discharge syndrome.